2005
DOI: 10.1016/j.ijgo.2005.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus (HPV) DNA detection in self-collected urine

Abstract: The use of urine coupled with its dry collection as 'paper smear' facilitating their easy transport, storage and direct PCR detection of HPV DNA opens up an alternative non-invasive approach for population screening of HPV infection, at least in such cases as children and infants in whom invasive samples are difficult to obtain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 23 publications
1
45
0
Order By: Relevance
“…Midstream urine-i.e., the standard for the diagnosis of metabolic diseases and urinary tract infections-is preferred by some authors, since it is thought to contain less PCR inhibitors. Three studies using midstream urine did not report on human DNA detection [45,46,50].…”
Section: Urine Samplingmentioning
confidence: 99%
“…Midstream urine-i.e., the standard for the diagnosis of metabolic diseases and urinary tract infections-is preferred by some authors, since it is thought to contain less PCR inhibitors. Three studies using midstream urine did not report on human DNA detection [45,46,50].…”
Section: Urine Samplingmentioning
confidence: 99%
“…Unlike cytology, HPV testing is amenable to simplified approaches for sample collection, including self-collected vaginal samples and urine-based sampling. These approaches may offer alternatives to clinic-based screening and improve access to care, particularly for hard-to-reach populations (2)(3)(4)(5)(6)(7)(8)(9)(10)(11). While urine-based screening offers simplicity in sample collection, there are few studies of clinical performance of urine-based sampling and HPV genotypes detectable by this approach compared to that of cervical and external genital sampling in relation to rigorously confirmed cervical disease status.…”
mentioning
confidence: 99%
“…All the cervical samples collected from Perdoor women were HPV DNA positive showing 100%concordance. Another study by Prusty et al also found 100% agreement in HPV positivity between cervical and urine samples (Prusty et al, 2005). A metaanalysis study comparing the sensitivity and specificity of Pap smear and HPV DNA found better sensitivity and specificity of HPV-DNA testing in the order of 94.6% and 94.2% (Koliopoulos et al, 2007).…”
Section: Discussionmentioning
confidence: 94%